PENGARUH UKURAN PERUSAHAAN TERHADAP KONSERVATISME AKUNTANSI DENGAN LEVERAGE SEBAGAI VARIABEL PEMODERASI - Sumiari, Kadek Nita; Wirama, Dewa Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
The purpose of this study is to analyze the effect of firm size on accounting conservatism and leverage as moderating variable between firm size and accounting conservatism. In this study, conservatism is measured by Earning/Accrual Method (Zhang Model), firm size is measured by ln total assets, and leverage is measured by debt to equity ratio. The Companies listed on the Indonesia Stock Exchange during the years 2009-2013 was used as population and the total sample are 215 companies. Data analysis techniques are used simple linear regression method and Moderated Regression Analysis (MRA). The results show that firm size has no effect on accounting conservatism, while leverage act as a moderating variable in the relationship between firm size and accounting conservatism.
Keywords: Accounting Conservatism, Firm Size, Leverage